Importance of Happiness and Meaningfulness of Work in Increasing Work Engagement of Millennial Generation in the Digital Age: Systematic Literatur Review - Elza Kusumawati; Andik Matulessy; Rr. Amanda Pasca Rini; Abdul Muhid (Jurnal Psikologi Teori dan Terapan, 2024)
Abstract Background: The mixing of 3 generations (x, millennial / y and z) in the world of work raises differences in the picture of work ethos and attachment. The company has a strategy of creating superior employees. Millennial employees show a desire to be appreciated, maximize work time and prioritize mental health, so that employees can still work in happy conditions and not depressed. Objective: This research shows the importance of happiness and work meaning felt by millennial employees to increase work engagement to the global competition. Method: Systematic literature review by identifying, assessing, and synthesizing literature search results through Google Scholar, Scopus, Research Gate, and Garuda. Results: 12 literature studies show that the work attachment of millennial generation employees is at a moderate level and is still below the work attachment of previous generations. Conclusion: Companies can provide work comfort and opportunities to be actively involved in work so that a sense of meaning arises for the work done to increase employee engagement in the company.   Abstrak Latar Belakang: Percampuran 3 golongan generasi (x, milenial/y dan z) di dunia kerja menunculkan perbedaan gambaran etos dan keterikatan kerja. Perusahaan memiliki strategi menciptakan karyawan unggul. Karyawan milenial menunjukkan keinginan untuk dihargai, memaksimalkan waktu kerja dan mengutamakan kesehatan mental, sehingga karyawan tetap bisa bekerja dalam kondisi bahagia dan tidak tertekan. Tujuan: Penelitian ini mengetahui pentingnya kebahagiaan dan kebermaknaan kerja yang dirasakan oleh karyawan milenial terhadap peningkatan keterikatan kerja pada persaingan global. Metode: yang digunakan adalah Systematic literatur review dengan mengidentifikasi, menilai dan menyintesiskan hasil penelusuran kepustakaan melalui google scholar, Scopus, research gate dan garuda. Hasil: 12 studi kepustakaan menunjukkan bahwa keterikatan kerja yang dimiliki para karyawan generasi milenial berada di taraf sedang dan masih di bawah keterikatan kerja yang  dimiliki para generasi sebelumnya. Kesimpulan: Perusahaan dapat memberikan kenyamanan kerja dan kesempatan untuk terlibat aktif dalam bekerja sehingga muncul rasa bermakna atas pekerjaan yang dilakukan sehingga dapat meningkatkan keterikatan kerja karyawan di perusahaan.